2020
DOI: 10.4081/oncol.2020.456
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll like receptor in progression and suppression of oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common type of head and neck squamous cell carcinoma and one of the multifactorial process that consists of most contributing factors such as tobacco smoking, chewing and alcohol consumption that altered the intracellular environment. Recent studies have shown relevance of Toll like receptor (TLR) associated with carcinogenesis. This review aim’s to explore that how TLR associates with progression and suppression of OSCC. This review is a classical review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
(75 reference statements)
3
5
0
Order By: Relevance
“…In the present study, a significant increase in the expression of TLR4 and MyD88 in OSCC was observed. This result is consistent with the results of Sharma and Bala ( 38 ). The TLR4/MyD88 signaling pathway activates the expression of NF-κB ( 39 ) and secondarily promotes the expression of pro-inflammatory genes, thereby triggering the inflammatory response of the host.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, a significant increase in the expression of TLR4 and MyD88 in OSCC was observed. This result is consistent with the results of Sharma and Bala ( 38 ). The TLR4/MyD88 signaling pathway activates the expression of NF-κB ( 39 ) and secondarily promotes the expression of pro-inflammatory genes, thereby triggering the inflammatory response of the host.…”
Section: Discussionsupporting
confidence: 94%
“…This suggests that overexpression of MyD88 is involved in tumor differentiation. The results are consistent with the results of Sharma and Bala ( 38 ), who also reported that high expression of TLR4 was associated with deep tumor invasion. He et al ( 42 ) indicated that activation of the TLR4-MyD88-NF-κB signaling pathway may stimulate epithelial-mesenchymal transition (EMT), which allows cancer cells to detach from the primary site and then invade lymphatic and/or blood vessels, resulting in loss of epithelial adhesion and polarity of cancer cells and promote tumor metastasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that TLR2 was connected with occurrence and prognosis of LSCC (19). TLR2 signaling pathway was found to be involved in promoting tumor cell movement via activation of the NF-κB pathway in breast and oral cancer (20,21).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that TLR2 was connected with occurrence and prognosis of LSCC ( 19 ). TLR2 signaling pathway was found to be involved in promoting tumor cell movement via activation of the NF-κB pathway in breast and oral cancer ( 20 , 21 ). In addition to gastric cancer, high expression of TLR2 was related to up-regulation anti-apoptotic and down-regulation tumor suppressor genes, which predicts poor prognosis ( 22 ).…”
Section: Discussionmentioning
confidence: 99%